Effect of garlic extract as a natural preservative based on protein profile of red snapper - Meutia Srikandi Fitria; Resta Afinda; Aprilia Indra Kartika (Universitas Gadjah Mada, 2025)
Red snapper (Lutjanus bitaeniatus) is a source of animal protein with a high-water content, making it prone to spoilage. Spoilage can be prevented through preservation. Garlic can be used as a natural preservative for fish because it contains antibacterial substances, including allicin, which plays a role in inhibiting and killing spoilage bacteria, as well as other antimicrobial compounds such as alkaloids, flavonoids, saponins, and tannins. This study aims to determine the effect of garlic extract as a natural preservative on the protein profile of red snapper. The research design was divided into five parts: fresh red snapper stored for 24 hours without soaking, and three parts soaked in garlic extract at concentrations of 5%, 10%, and 20%, respectively. This type of research was experimental. The research method was the preparation of garlic extract at concentrations of 5%, 10%, and 20%. Protein concentration was calculated using the Bradford method, followed by SDS-PAGE to separate proteins based on their molecular weight. The SDS-PAGE results were analyzed using the GelAnalyzer 19.1 application to calculate the molecular weight of the proteins and the protein profiles of the treatments compared to fresh fish. The results showed that the highest protein concentration was found in the 5% garlic extract treatment compared to the 10% and 15% concentrations. The protein profiles of fresh snapper and the 5% garlic extract treatment were not significantly different from fresh red snapper, with 13 protein bands (9 major bands and four minor bands). In contrast, fresh red snapper had 16 protein bands (13 major and three minor bands). This study concludes that garlic extract immersion treatment can be used as a natural preservative, with the optimal concentration being 5% garlic extract.